Low Cost Airlines in a Developing Economy: The Case of India - Pasari, Nitika (2006)
This dissertation is a study on the low cost airlines in a developing country, particularly the case of India, since the writer of this dissertation is an Indian. It begins with introducing the emergence of low cost airlines all around the world, which began with the US and was followed by Europe, before coming to Asia. It talks about the factors that initiated the emergence of low cost airlines, particularly, the deregulation of the air transport industry and the technological changes along with internet. It moves on to describe the economy of India dating back to the British colonial rule, how the economy has transformed today, from a poor country to the fastest growing economy in the world. A brief overview of the other modes of transport dominant in the country is given, especially the Indian Railways, followed by a detailed study of the Airline Industry in India, its deregulation, various policy changes that took place from time to time, the emergence of low cost airlines with a brief description of the low cost airlines operating in India. Subsequently, it deals with a research done by the author to give her contribution in this field of study. The analysis is divided into two parts. The first part deals with a primary research undertaken by the author with the help of questionnaires to find out customer attitude towards low cost airlines. The second part is a secondary research with has been analyzed in further detail to support the primary research. Finally, the conclusion gives a general idea of the main findings of the research along with some policy recommendations to the industry as a whole.